UPAYA PENINGKATAN ANGKA KELENGKAPAN CATATAN PENERIMAAN PESAN MEDIS PADA UNIT KEPERAWATAN RSI UNISMA MALANG - Saptono Putro; Lukman Hakim; Tri Wahyu Sarwiyata (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2018)
The purpose of this study is to identify the root of the problems that make RSI Unisma MalangNursing Unit has not been able to achieve the standard of Medical Message Receipt Recordscompletion, and to find alternative solutions that can be applied to overcome the problems. The typeof this research is descriptive qualitative. The research data is qualitative data obtained using 3methods of data collection, that is interview, observation, and documentation. Research data wereanalyzed using Fishbone diagram and USG method. The results show that the main root of theproblem at RSI Unisma Malang is the SOP factor that is less relevant to the implementation. Themost appropriate solution to overcome this problem is to revise the SOP of patient acceptancerecording, followed by SPO resocialization, and monitoring of SPO implementation.